High Likelihood of Meningitis with Late Onset Septicemia in Newborn - Shahidullah, M; Mannan, MA; Alam, MS; Uddin, MZ; Dey, AC; Dey, SK (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Neonatal meningitis must be recognized and treated quickly to prevent death or disability. Incidence of neonatal meningitis with late onset sepsis is higher in developing countries than those of resource-rich countries. In neonates signs and symptoms of serious infections are often obscured and clinical examination cannot distinguish among septic babies with or without meningitis. Clinicians often differ whether neonates undergo lumber puncture or not to distinguish septic babies with or without meningitis. Abnormal CSF findings are often used to detect neonatal meningitis and determine the type and length of antibiotic therapy with proven sepsis and meningitis cases. This study was conducted to evaluate the bacterial meningitis among the late onset sepsis in newborns and to identify the clinical manifestations that can distinguish septicemia from meningitis in neonates. Total 1706 admitted patient in NICU of Bangabandhu Sheikh Mujib Medical University from January 2007 to December 2009 were evaluated retrospectively. Among the 133 (27.94%) cases of suspected late onset sepsis 47(35.33%) were proven sepsis, 63(47.37%) were probable sepsis and 23(17.29%) cases were clinical sepsis based on clinical features laboratory reports and blood cultures. Among the proven sepsis 12(42.85%) cases were found to have definitive bacterial meningitis and 16(57.15%) were probable bacterial meningitis. Among the provable sepsis only 1(12.50%) cases were found to have definite bacterial meningitis and 7 (87.50%) cases were probable bacterial meningitis. There were no meningitis have found among the clinical sepsis. Neonatal meningitis frequently occurred in late onset sepsis. The most frequent presenting clinical features for meningitis cases are more or less similar to those of septicemic cases. The data of the study suggest that newborns with a positive blood culture are significantly more likely to have meningitis than those with a negative blood culture. DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11362 J Bangladesh Coll Phys Surg 2012; 30: 17-23